Coping strategies employed by public psychiatric healthcare workers during the COVID-19 pandemic in southern Gauteng, South Africa. - Ann Scheunemann; Andrew W Kim; Aneesa Moolla; Ugasvaree Subramaney (PLoS ONE)
Within the context of the novel coronavirus pandemic and new challenges to a resource-constrained public healthcare system, many healthcare workers in South Africa have faced numerous stressors that have compromised their mental health. While the current literature on COVID-19 in South Africa highlights the widespread psychosocial stress experienced by healthcare workers during the pandemic, little is known about the coping strategies utilized to continue service delivery and maintain one's mental health and well-being during this ongoing public health emergency. In this study, we sought to explore the coping strategies used by healthcare workers employed in the public psychiatric care system in southern Gauteng, South Africa during the coronavirus disease (COVID-19) pandemic. Psychiatric healthcare workers (n = 55) employed in three tertiary public hospitals and two specialized psychiatric facilities participated in in-depth interviews between July 2020 and March 2021. We found that coping strategies spanned multi-level and multi-systemic efforts. Intrapersonal, interpersonal, material, and structural coping were mapped across individual, family, and hospital systems. The most commonly utilized coping strategies included positive mindsets and reappraisal, social support systems, and COVID-19 specific protections. Findings also highlighted the contextual and interconnected nature of coping. Healthcare workers applied multiple coping strategies to combat the negative mental health effects of the COVID-19 pandemic. Better understanding these strategies, contexts in which they are employed, and how they interact can be used to develop evidence-based interventions to support healthcare workers experiencing healthcare-related stressors during the COVID-19 pandemic.